COLLOCATIONS FOUND IN THE DIALOGUE TEXTS WRITTEN BY THE ELEVENTH GRADE STUDENTS OF MAN 1 KUDUS - Della Futika Putri; Muh Syafei; Mutohhar Mutohhar (Universitas Muria Kudus, 2023)
Lexical collocation is one of the grammar material in English subjects that is taught by the English teacher for the eleventh grade students in the High School. Therefore, it is important to analyze the students’ level of understanding after learning the material. This research aims to classify the types of lexical collocation and to find out the students’ ability in writing dialogue text using lexical collocations. In this research, the descriptive qualitative was used as a research design. The writer did documentation as data collection technique. The participants of this research were the XI MIPA 6 students of MAN 1 Kudus in the academic year 2021/2022. The writer had analyzed 13 dialogue texts written by the students who worked in a pair. The findings show that there are seven types of lexical collocation found, those are verb with preposition + noun/pronoun (8.93%), verb + noun (19.64%), adjective + noun (35.71%), noun + verb (1.79%), noun + noun (25%), adverb + adjective (1.79%), and verb + adverb (7.14%). Moreover, the percentage of the correct lexical collocations shows that the students have excellent skills in writing dialogue text using lexical collocations.